THE INFLUENCE OF CLEFT LIP AND PALATE SEVERITY ON SURGICAL OUTCOMES - Asparini, Ruby Riana; Nur Khalida Zia; Sidharta, Bragastio; Sakthivel, Jeyasree; Naga, Bhuvana Sri (Jurnal Rekonstruksi dan Estetik, 2023)
Highlights: The severity of unilateral CLP was assessed by categorizing preoperative photo data based on the severity of the cleft, and this severity was then correlated with the surgical outcomes. The way wounds heal is influenced by the width of the gap and suture tension, which are crucial factors in determining surgical outcomes. Abstract: Introduction: An orofacial cleft is a congenital abnormality in which an abnormal opening or cleft of the lips and/or palate. Data in 2017 showed that the most encountered characters are patients with cleft lip and palate. The distribution of the incidence of cleft lip and palate at Cleft Lip and Palate (CLP) Center Faculty of Medicine University of Muhammadiyah Malang was dominated by the complete unilateral type, which was 45.22%. Generally, the severity of cleft lip and/or palate is influenced by the severity of the preoperative cleft. Methods: This study used a retrospective cohort design taken from 40 medical records at Cleft Lip and Palate (CLP) Center Faculty of Medicine University of Muhammadiyah Malang. The preoperative photo data were categorized according to the severity of the cleft, then postoperative photos were assessed according to the Visual Rating Chart (VRC) indicator. Results: The intraclass correlation coefficient (ICC) reliability test between evaluators has a strength of > 0.8 on the outcome of lip and nose surgery and also > 0.9 on the outcome of the palate, indicating that there was no perception gap between evaluators. The Mann-Whitney non-parametric test had a significance of p < 0.05, indicating that there was a positive correlation between the severity of unilateral cleft lip and palate and the outcome of surgery. Conclusion: There is a correlation between the severity of the unilateral cleft lip and palate and the surgical outcome.